The longitudinal relation between brain lesion load and atrophy in multiple sclerosis: a 14 year follow up study. Issue 11 (14th November 2003) - Chard, D T; Brex, P A; Ciccarelli, O; Griffin, C M; Parker, G J M; Dalton, C; Altmann, D R; Thompson, A J; Miller, D H
Abstract : Background: Studies have suggested that T2 lesion activity is prominent in early relapsing-remitting multiple sclerosis, whereas brain atrophy, while seen early, appears more evident in later progressive disease. The temporal relation between these processes remains unclear. Objective: To explore the association between changing brain lesion loads and subsequent tissue atrophy in multiple sclerosis. Methods: 28 subjects with clinically probable or definite multiple sclerosis (mean age 46.0 years; 17 female and 11 male) were followed for 14 years after first onset of symptoms. T2 lesion loads were estimated soon after symptom onset and at around five, 10, and 14 years later. Disease related atrophy was estimated at the 14 year follow up by comparing brain tissue volumes (proportional to total intracranial volumes) determined in the multiple sclerosis group with data from 29 normal control subjects (mean age 36.7 years; 16 female, 13 male) using multiple linear regression analyses to allow for differences in age and sex distributions. Results: Change in lesion load in the first five years was more closely correlated to disease related brain atrophy at 14 years than later changes in lesion load, although the correlation was only moderate (Spearman correlation  =  −0.528, p = 0.004). Conclusions: From this, it appears that early rather than later focal lesion accumulation relates to subsequent brain atrophy, but factors unconnected directly with lesion formation probably also play a significant role in determining such atrophy.